Functionalized chitosan derivatives as nonviral vectors: Physicochemical properties of acylated N,N,N-trimethyl chitosan/oligonucleotide nanopolyplexes - Santos, J (2015)
Cationic polymers have recently attracted attention due to their proven potential for nonviral gene delivery. In this study, we report novel biocompatible nanocomplexes produced using chemically functionalized N,N,N-trimethyl chitosan (TMC) with different N-acyl chain lengths (C 5 -C 18 ) associated with single-stranded oligonucleotides. The TMC derivatives were synthesized by covalent coupling reactions of quaternized chitosan with n-pentanoic (C 5 ), n-decanoic (C 10 ), and n-octadecanoic (C 18 ) fatty acids, which were extensively characterized by Fourier transform-infrared spectroscopy (FT-IR) and proton nuclear magnetic resonance ( 1 H NMR). These N-acylated TMC derivatives (TMC n ) were used as cationic polymeric matrices for encapsulating anionic 18-base single-stranded thiophosphorylated oligonucleotides (ssONs), leading to the formation of polyplexes further characterized by zeta potential (ZP), dynamic light scattering (DLS), binding affinity, transfection efficiency and in vitro cytotoxicity assays. The results demonstrated that the length of the grafted hydrophobic N-acyl chain and the relative amino:phosphate groups ratio (N/P ratio) between the TMC derivatives and ssON played crucial roles in determining the physicochemical properties of the obtained nanocomplexes. While none of the tested derivatives showed appreciable cytotoxicity, the type of acyl chain had a remarkable influence on the cell transfection capacity of TMC-ssON nanocomplexes with the derivatives based on stearic acid showing the best performance based on the results of in vitro assays using a model cell line expressing luciferase (HeLa/Luc705).